Cost analysis and benefits of opt-out HIV testing at a tertiary care centre in northern India. (April 2014) - Minz, Ranjana W; Khairwa, Anju; Aggarwal, Ritu; Kaur, Harwinder; Singh, Surjit; Sharma, Aman; Varma, Subhash; Mathuria, SN; Pasricha, Neelam
Currently, in India, the National AIDS Control Organization does not recommend HIV screening for all patients attending health care facilities. The objective of study was to evaluate cost and benefits of opt-out HIV testing at a tertiary care hospital from India. This is a retrospective cohort study of patients who had undergone HIV testing. The cost for HIV testing and cost per HIV-infected patient were determined. A total of 6512 patients (66.4% men and 905 patients younger than 14 years) with mean (SD) age of 30.3 (20.7) years were tested for HIV infection during the study period. Overall, 137 (2.1%) patients tested positive for HIV infection. Total cost for performing HIV tests during study period was Indian Rupees (INR) 649, 319 (US dollar [USD] 11805.8). The estimated cost per person tested was INR 99.71 (USD1.8) and cost per HIV-infected patient identified and referred to the antiretroviral therapy centre was INR 4739.55 (USD86.2). We determined a 2.1% period prevalence estimate for HIV infection. Based on cost per HIV-infected patient identified and referred to the antiretroviral therapy centre and the burden of HIV infection, it may be cost effective to perform routine opt-out screening for HIV infection in all patients attending health care facilities in developing countries like India.